Pengaruh Kepemimpinan Kepala Sekolah dan Kolaborasi Guru Terhadap Kinerja Guru Pada Sekolah Taman Kanak-Kanak: Sebuah Systematic Literature Review - Ismi Susanti (Yayasan Sembilan Pemuda Indonesia, 2025)
This study analyzes the influence of school principal leadership and teacher collaboration on teacher performance in kindergartens. In the educational context, school principal leadership plays a crucial role in fostering an environment that supports teachers’ professional development, while collaboration among teachers is expected to enhance teaching effectiveness and performance. This research employs a Systematic Literature Review (SLR) approach to identify, evaluate, and synthesize findings from relevant studies published over the past two decades. A total of 20 studies were reviewed to provide a comprehensive overview of the relationships among the investigated variables. The analysis reveals that transformational, democratic, and supportive leadership styles of principals positively influence teacher performance. Furthermore, teacher collaboration, including regular meetings, group discussions, and joint training, significantly contributes to the development of teachers’ skills and motivation. This study suggests that principals should adopt collaborative leadership styles and facilitate opportunities for effective teacher collaboration. Intensive collaboration among teachers can accelerate knowledge exchange and best practice sharing, ultimately improving teaching quality in kindergartens. Further research is encouraged to explore additional factors that influence teacher performance in early childhood education settings.